2017
DOI: 10.1038/srep45998
|View full text |Cite
|
Sign up to set email alerts
|

Dark trions and biexcitons in WS2 and WSe2 made bright by e-e scattering

Abstract: The direct band gap character and large spin-orbit splitting of the valence band edges (at the K and K’ valleys) in monolayer transition metal dichalcogenides have put these two-dimensional materials under the spot-light of intense experimental and theoretical studies. In particular, for Tungsten dichalcogenides it has been found that the sign of spin splitting of conduction band edges makes ground state excitons radiatively inactive (dark) due to spin and momentum mismatch between the constituent electron and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 30 publications
2
37
1
Order By: Relevance
“…The prefactor η summarizes differences in for instance resonance enhancement [51,52] and optical material properties [53,54], and can be determined from an experiment at a known temperature. To determine η, we further make the assumption that before In monolayer WS2 the dark exciton state is formed by the electrons in the conduction band and holes in the valence band with opposite spins, and the energy of this dark exciton state is slightly lower (30-50 meV) than the bright exciton state [55][56][57][58][59]. Since relaxation from the bright to the dark exciton state requires a spin flip of the electrons, this process is expected to be substantially slower than the exciton cooling process but cannot be excluded on the basis of the current experiments.…”
Section: Resultsmentioning
confidence: 99%
“…The prefactor η summarizes differences in for instance resonance enhancement [51,52] and optical material properties [53,54], and can be determined from an experiment at a known temperature. To determine η, we further make the assumption that before In monolayer WS2 the dark exciton state is formed by the electrons in the conduction band and holes in the valence band with opposite spins, and the energy of this dark exciton state is slightly lower (30-50 meV) than the bright exciton state [55][56][57][58][59]. Since relaxation from the bright to the dark exciton state requires a spin flip of the electrons, this process is expected to be substantially slower than the exciton cooling process but cannot be excluded on the basis of the current experiments.…”
Section: Resultsmentioning
confidence: 99%
“…The dark exciton states at higher excited states have also been observed in 1L WS 2 at the excitation wavelength of 990 nm and 10 K via two‐photon excitation spectroscopy . Moreover, dark trions and biexcitons have also been predicted in 1L WS 2 , which can be optical bright by introducing the intervalley electron and electron scattering . Furthermore, Danovich et al have suggested that Auger recombination processes of dark excitons may take responsibilities for the low PL quantum efficiency of 1L WS 2 .…”
Section: Luminescence Beyond Fundamental Excitonic Emission Of 2d Ws2mentioning
confidence: 93%
“…In particular, the electronelectron contact PDF for the semidark trion and biexciton in tungsten-based TMDCs determines the coupling strength of the dark and bright states as µ bd ∝ g ee (0) and hence determines the recombination rates of the semidark states. 33 3 EX is the total energy of an exciton. The lines show the frequency relative to the bright exciton peak arising due to the recombination of a single electron-hole pair in each complex: see Sec.…”
Section: Contact and Exchange Interactions Between Charge Carriersmentioning
confidence: 99%